The Principle of Legal Relationship Between Syari’ah Banks and Customers Saving Their Money - Sri Astutik (Fakultas Hukum Universitas Hang Tuah, 2017)
Saving money in syari‟ah banks may be conducted through aqad Wadiah and aqad Mudharabah, in the form of wadiah giro, wadiah saving, mudharabah saving, mudharabah deposit, and other financial products in line with the syari‟ah of Islam. The legal relationship between syari‟ah banks and customers saving their money is an agreement specifically mentioned in a written contract about saving some money in syari‟ah banking, and it is called Aqad (i.e., contract). In financial collection, therelationship between syari‟ah banks and the customers (depositor) is in the form ofpartnership. The principle underlying that partnership is the principle of trust andamanah.